Combinatorial Polyacrylamide Hydrogels for Preventing Biofouling on Implantable Biosensors. Issue 24 (12th May 2022) - Chan, Doreen; Chien, Jun‐Chau; Axpe, Eneko; Blankemeier, Louis; Baker, Samuel W.; Swaminathan, Sarath; Piunova, Victoria A.; Zubarev, Dmitry Yu.; Maikawa, Caitlin L.; Grosskopf, Abigail K.; Mann, Joseph L.; Soh, H. Tom; et al.
Abstract: Biofouling on the surface of implanted medical devices and biosensors severely hinders device functionality and drastically shortens device lifetime. Poly(ethylene glycol) and zwitterionic polymers are currently considered "gold‐standard" device coatings to reduce biofouling. To discover novel anti‐biofouling materials, a combinatorial library of polyacrylamide‐based copolymer hydrogels is created, and their ability is screened to prevent fouling from serum and platelet‐rich plasma in a high‐throughput parallel assay. It is found that certain nonintuitive copolymer compositions exhibit superior anti‐biofouling properties over current gold‐standard materials, and machine learning is used to identify key molecular features underpinning their performance. For validation, the surfaces of electrochemical biosensors are coated with hydrogels and their anti‐biofouling performance in vitro and in vivo in rodent models is evaluated. The copolymer hydrogels preserve device function and enable continuous measurements of a small‐molecule drug in vivo better than gold‐standard coatings. The novel methodology described enables the discovery of anti‐biofouling materials that can extend the lifetime of real‐time in vivo sensing devices. Abstract : Hydrogel formulations that prevent protein and platelet adhesion in assays where "gold‐standard" polymers exhibit significant platelet adhesion are identified. By using machine‐learning techniques to analyze molecular features of the polyacrylamide‐based copolymers, features giving rise to this anti‐biofouling performance are identified. Coating electrochemical devices with these top‐performing polyacrylamide‐based hydrogels extend lifetime when implanted intravenously and enable in vivo real‐time monitoring of analytes.